2006
DOI: 10.1002/app.25217
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of the chain packing between poly(ethylene isophthalate) chains via coalescence from their inclusion compound formed with γ‐cyclodextrin

Abstract: Amorphous poly(ethylene isophthalate) (PEI) was synthesized, and was used for preparing an inclusion compound (IC) with g-cyclodextrin (g-CD). Coalesced polymer was produced by washing the PEI-g-CD-IC with hot water. Wide angle X-ray diffraction, Fourier transform infrared, and differential scanning calorimetry analyses were employed to verify formation of PEI-g-CD-IC and to compare the as-synthesized and coalesced PEI samples. These observations suggested that the conformations and morphology/ chain-packing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Their results are consistent with our observations16, 49, 58 that amorphous polymer samples coalesced from their CD‐IC crystals, with initially largely extended chains that rapidly randomly coil, but without complete entanglement, exhibit T g s that are elevated above those obtained from their randomly coiling and entangled solutions and melts. Furthermore, Mei et al75 observed that annealing the single chain PAL globules at 220 °C for 30 min, which is ∼20 °C above their T g , did not, when subsequently heated, result in a T g reduction.…”
Section: Coalesced Neat Polymerssupporting
confidence: 92%
See 2 more Smart Citations
“…Their results are consistent with our observations16, 49, 58 that amorphous polymer samples coalesced from their CD‐IC crystals, with initially largely extended chains that rapidly randomly coil, but without complete entanglement, exhibit T g s that are elevated above those obtained from their randomly coiling and entangled solutions and melts. Furthermore, Mei et al75 observed that annealing the single chain PAL globules at 220 °C for 30 min, which is ∼20 °C above their T g , did not, when subsequently heated, result in a T g reduction.…”
Section: Coalesced Neat Polymerssupporting
confidence: 92%
“…Furthermore, Mei et al75 observed that annealing the single chain PAL globules at 220 °C for 30 min, which is ∼20 °C above their T g , did not, when subsequently heated, result in a T g reduction. This is very reminiscent of the high temperature temporal stabilities shown by amorphous polymers coalesced from their CD‐ICs, which also exhibit elevated T g s 16, 49, 58. In both cases, it seems that achievement of complete chain entanglement is an extremely slow process even at temperatures well above the glass transition.…”
Section: Coalesced Neat Polymersmentioning
confidence: 94%
See 1 more Smart Citation
“…The glass transition temperature of poly(ethylene isophthalate) (PEI) coalesced from its γ-CD-IC is ∼15-20 • C higher (∼70 • C) than that of the as-synthesized PEI, though both appear completely amorphous [58]. Typically polymer chains in amorphous regions start to move at the glass transition temperature.…”
Section: Pei [58]mentioning
confidence: 99%
“…In the past several years, we have demonstrated that it is possible to obtain bulk polymer samples whose structures, morphologies, and even chain conformations are significantly altered from those obtained by processing randomly coiling, entangled polymers from their solutions and melts by the usual techniques. By first forming inclusion compound (IC) crystals between guest polymers and host cyclodextrins (CDs),1–72 and then coalescing the guest polymer chains from the polymer‐CD‐ICs through removal of the host CD crystalline lattice,10, 11, 17–23, 25, 27, 28, 30–35, 37–41, 44–46, 51 we find the resulting coalesced bulk samples to be significantly reorganized. For example, we generally observe that (i) crystallizable homopolymers coalesced from their CD‐ICs evince increased levels of crystallinity, unusual polymorphs, and higher melting, crystallization, and decomposition temperatures,21, 23, 27, 31, 32, 37, 40 while coalesced amorphous homopolymers exhibit higher glass transition temperatures17, 22, 47 than samples consolidated from their disordered solutions and melts; (ii) molecularly mixed, intimate blends of two or more polymers that are normally believed to be immiscible can be achieved by coalescence from their common CD‐IC crystals,10, 17, 22, 28, 33, 34, 38, 44, 48 (iii) the phase segregation of incompatible blocks can be controlled (suppressed or increased) when block copolymers are coalesced from their CD‐IC crystals,18, 20, 25, 35 and (iv) the thermal and temporal stabilities of the well‐mixed homopolymer blends and block copolymers obtained by coalescence from their CD‐ICs appear to be substantial,10, 17, 21, 32, 33, 38, 44 thereby suggesting retention or reformation of their as‐coalesced structures and morphologies under normal thermal processing conditions.…”
Section: Introductionmentioning
confidence: 98%